Origin and evolution in the genus Avena: implications in the plant breeding - Zanettini, Maria Helena Bodanese; de Carvalho, Fernando I. F. (Pesquisa Agropecuaria Brasileira, 1993)
Oat originated in Asia Minor or North Africa. It developed as a second-degree culture at North and West Europe, as an invader plant in season main cultures as wheat and barley. The Avena species have three degrees of ploidia: diploids (2n = 2x = 14), tetraploids (2n = 4x = 28) and hexaploids (2n = 6x = 42), all having regular meiosis. Inside each degree of ploidia there are cultivated forms which survive only under human care. Phylogenetic relations between Avena species are not completely stablished. Autopolyploidy, segmental alopolyploidy, as well as structural changes in chromosomes seem to have had relevant contribution in the evolution of this genus. This review presents a synopsis of the present knowledge about relations between the different species of Avena.